2019
DOI: 10.3389/fnagi.2019.00027
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Reveals Mitigation of Cerebrovascular Dysfunction by Bradykinin Receptors 1 and 2 Inhibitor Noscapine in a Mouse Model of Cerebral Amyloidosis

Abstract: Functional magnetic resonance imaging (fMRI) techniques can be used to assess cerebrovascular dysfunction in Alzheimer’s disease, an important and early contributor to pathology. We hypothesized that bradykinin receptor inhibition alleviates the vascular dysfunction in a transgenic arcAβ mouse model of cerebral amyloidosis and that fMRI techniques can be used to monitor the treatment response. Transgenic arcAβ mice, and non-transgenic littermates of 14 months-of-age were either treated with the bradykinin rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…Studies in animal models of cerebral amyloidosis have reported age-dependent reductions in rCBF ( Fig. 3b) [46,[49][50][51][82][83][84]. Interestingly, hyperperfusion was found in the rTG4510 mouse model of tauopathy [85], but have so far not been reported for models of cerebral amyloidosis.…”
Section: Dysregulation Regional Rcbf and Volumementioning
confidence: 95%
See 1 more Smart Citation
“…Studies in animal models of cerebral amyloidosis have reported age-dependent reductions in rCBF ( Fig. 3b) [46,[49][50][51][82][83][84]. Interestingly, hyperperfusion was found in the rTG4510 mouse model of tauopathy [85], but have so far not been reported for models of cerebral amyloidosis.…”
Section: Dysregulation Regional Rcbf and Volumementioning
confidence: 95%
“…Vascular remodelling has been also described to occur in animal models of cerebral amyloidosis [46][47][48], where some of the strains also display CAA [24,31,47,[49][50][51]. A recent study described changes in vessel den-sity and morphology in a transgenic model of tauopathy [52].…”
Section: The Interplay Between Vascular Remodelling and Cerebral Hemomentioning
confidence: 99%
“…Severe cerebral amyloid angiopathy is also present by 9 to 15 months of age, with dense Aβ aggregates accumulating in the walls of blood vessels (42). Cerebral amyloid angiopathy leads to hypoperfusion, impaired vascular reactivity, decreased vessel density, blood-brain barrier 6 impairment and occurrence of cerebral microbleeds (36,(43)(44)(45)(46). Animals were housed in ventilated cages inside a temperature-controlled room, under a 12-hour dark/light cycle.…”
Section: Animal Modelmentioning
confidence: 99%
“…MRI was performed as described previously [27,44]. To reduce field inhomogeneities, global 1 st -order followed by fieldmap-based local shimming on the mouse brain was performed.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%